International Ski and Snowboard Federation (FIS) consensus statement on return-to-performance in competitive alpine and freestyle skiers and snowboarders - Spörri, J.; Müller, P. O.; Bonell Monsonís, O.; Bahr, R.; Beck, L.; Brucker, P. U.; Engbretsen, L.; Fink, C.; Hörterer, H.; Jordan, M. J.; Mitterbauer, G.; Moksens, H.; et al. (BMJ Open Sport & Exercise Medicine, 2026)
Returning to a high level of performance after injury is a significant challenge for athletes. However, current best practices for return-to-performance in competitive snow sports are not well understood due to a lack of research evidence and international harmonisation. The International Ski and Snowboard Federation commissioned this consensus statement to provide recommendations for the safe and successful return of competitive alpine and freestyle skiers and snowboarders to competitive performance. An international consensus panel was formed to contribute their knowledge and perspectives on return-to-performance. The panel included experts with extensive experience in return-to-performance. The panel consisted of 23 experts (7 women and 16 men) from various skiing and snowboarding disciplines and levels of competition. It included 16 researchers, 6 snow sports or International Olympic Committee officials, 9 physicians, 6 physical therapists, 2 sports psychologists, 2 coaches and 2 former athletes, some of whom had two backgrounds/functions. However, it was disproportionately European (78%) and North American (13%), with minimal representation from South America (4%) and Africa (4%) and no representation from Asia or Australasia. The RAND-UCLA Appropriateness Method was adopted for the underlying consensus process. First, the panel discussed which topics and questions should be included in the consensus statement before developing an overall structure. The consensus process then involved providing key content based on the literature or statements from experts/panel members. These were voted on three times by all the panel members, resulting in a list of 196 statements. The jointly developed overall structure and the final statement list then formed the basis for preparing the manuscript. This consensus statement aims to assist athletes, coaches and medical staff of international and national federations in planning and implementing safe and successful return-to-performance strategies for competitive alpine and freestyle skiers and snowboarders.